(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community development is intended to assess the effectiveness of a 12-week training management approach grounded in the Long-Term Athlete Development (LTAD) framework, executed at the Surabaya Athletes Association. The program aims to improve athletic performance while comprehensively addressing the developmental requirements of student-athletes. Thirty student-athletes, aged 13 to 17 years, engaged in the 12-week intervention. A mixed-method research methodology was utilized to perform a thorough study. Quantitative data were obtained using pre- and post-program physiological evaluations (VO2Max, strength, agility), while qualitative data were collected through surveys assessing motivation and program satisfaction. The quantitative study demonstrated a statistically significant enhancement in participants’ VO2Max values (p<0.05). Furthermore, there was a significant average gain of 12% in scores on strength and agility assessments. Over 85% of the participants qualitatively expressed improvement in training motivation and overall program satisfaction. The results robustly endorse the effectiveness of a training approach that methodically combines physical conditioning with academic requirements and mental health factors. This method successfully facilitated physiological and psychological improvements based on the principles of periodization and individualization. The study advocates implementing the LTAD scheme as a foundational framework for the national Indonesian Athletes Association to guarantee sustainable, high-performance athlete development.